Effects of cortisol on cognitive and emotional disorders after stroke: A scoping review - Wang, Tiantian; Li, Xuan; Jia, Yuanyuan; Zhang, Yuyao; Meng, Dianhuai (Heliyon, 2024)
Stroke-induced cognitive and mood disorders are closely related to glucocorticoids released during hypothalamic-pituitary-adrenal (HPA) axis activation. There are many studies on the relationship between cortisol levels and post-stroke cognitive impairment (PSCI) and post-stroke depression (PSD). This paper provides a scoping review of these studies to clarify the effect of cortisol on PSCI and PSD, thereby providing a theoretical basis for clinical diagnosis and treatment. We searched for literature published up to October 2023 on the association of cortisol with post-stroke cognitive and emotional disorders in the PubMed, Web of Science, Cochrane Library, CNKI and Wanfang databases. Relevant papers were identified and the effects of cortisol on cognitive and emotional disorders after stroke were analyzed by literature induction. Eighteen papers were included, including cross-sectional studies and cohort studies. The subjects suffered ischemic stroke or hemorrhagic stroke. Cortisol levels were measured from samples of blood, saliva or hair. Most patients showed increased basal cortisol levels and changes in cortisol circadian rhythms. Most studies report that patients with high cortisol levels on admission (acute phase of stroke) are more likely to experience cognitive decline and depression later in life. Admission cortisol level may be a promising biomarker for predicting cognitive and emotional prognosis after stroke. •Cortisol levels have an impact on cognition and emotion after stroke.•Exposed to highcortisol levels prior to onset were more likely to have delayed cognitive dysfunction and depression.•Cortisol is a promising biomarker for prognostic judgment.